Developmentally-Dynamic Murine Brain Proteomes and Phosphoproteomes Revealed by Quantitative Proteomics - Peter F. Doubleday; Bryan A. Ballif (Proteomes, 2014)
Developmental processes are governed by a diverse suite of signaling pathways employing reversible phosphorylation. Recent advances in large-scale phosphoproteomic methodologies have made possible the identification and quantification of hundreds to thousands of phosphorylation sites from primary tissues. Towards a global characterization of proteomic changes across brain development, we present the results of a large-scale quantitative mass spectrometry study comparing embryonic, newborn and adult murine brain. Using anti-phosphotyrosine immuno-affinity chromatography and strong cation exchange (SCX) chromatography, coupled to immobilized metal affinity chromatography (IMAC), we identified and quantified over 1,750 phosphorylation sites and over 1,300 proteins between three developmental states. Bioinformatic analyses highlight functions associated with the identified proteins and phosphoproteins and their enrichment at distinct developmental stages. These results serve as a primary reference resource and reveal dynamic developmental profiles of proteins and phosphoproteins from the developing murine brain.